Recent Advances in Child and Adolescent Psychiatry - Matteo Chiappedi; Martina Maria Mensi (MDPI AG, 2022)
The field of child and adolescent psychiatry is receiving growing attention, although a number of local differences still exist in terms of academic curricula, board certifications and even definitions of what is to be considered part of this field or not [...]